Analisis Strategi Partai Gerindra dalam Meningkatkan Elektabilitas Prabowo Subianto pada Pemilihan Presiden 2019 di Provinsi Aceh - Assad, Mohd; Amin, Muryanto; Nasution, Indra Kesuma (PERSPEKTIF, 2024)
This research aims to analyze the strategies employed by the Gerindra Party to enhance the electability of Prabowo Subianto in the 2019 presidential election in the Aceh Province, utilizing Organizational Theory, Social Exchange Theory, and Political Marketing Theory. The qualitative research method incorporated data collection techniques such as observation, interviews, and documentation. The findings indicate the success of Gerindra Party's organizational strategy in Aceh, leveraging organizational structure and the committed performance of party cadres, motivating them to collectively support Prabowo Subianto. The effectiveness of the political promise strategy is evident through the signing of a political contract between Prabowo Subianto and 26 Aceh religious figures, aimed at developing Aceh Province and realizing the Free Port of Sabang to boost the economy of Aceh's communities. Furthermore, the identity politics strategy was implemented due to the majority of Aceh's population being Muslim. The Gerindra Party crafted an image of Prabowo as a devout Muslim leader who is consistent, pro-people, and engaged religious Islamic authorities in garnering support through Islamic boarding schools, mosques, and associations in the Aceh Province. This approach strengthens the relationship between Prabowo Subianto, the Gerindra Party, and the Acehnese community.